Seminar dan Sosialisasi Bimbingan Remaja Usia Sekolah Untuk Penanaman Karakter Anti Bullying di SMP 5 Sawoo Ponorogo - Candra Febrilyantri; Astin Diassari; Umi Samsiyah; Zakiyah Faroza Firdaus (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Bullying is a repetitive aggressive act committed by a group or individual against a specific individual. This action is prone to occur during adolescence, as adolescents often struggle to cope with this transition effectively, resulting in psychological and social decline. The prevalence of bullying behaviors frequently reported in the mass media is one example of the issues facing adolescents. This occurs due to various factors, one of which is the weak character of adolescents in facing the transition to adulthood. The purpose of this community service activity is to assist adolescents in cultivating character traits to prevent bullying behavior. This activity utilizes the Asset Based Community Development (ABCD) method, which involves observation, preparation, implementation, and evaluation. The activity is carried out at SMP 5 Sawoo Ponorogo, chosen because it is a school located on the outskirts of the city and requires character education for adolescents, supported by the low literacy rate in this area. The results of the service include students at SMP 5 Sawoo receiving knowledge from speakers regarding anti-bullying, healthy self-concepts, adolescent challenges and issues, ultimately enabling them to build bridges of hope.